2021
DOI: 10.3390/socsci10070258
|View full text |Cite
|
Sign up to set email alerts
|

Employee Preparedness for Industry 4.0 in Logistic Sector: A Cross-National Study between Poland and Malaysia

Abstract: Today we are witnessing a paradigm shift when it comes to the industry. There are chances that Industry 4.0 does not only involve major changes in production and business solutions, but also the ability of many enterprises (mainly production companies) to come closer to developed economies. This article highlights the aspect of creating new business models that integrate organizations around Industry 4.0 solutions and create new value for the client and internal client. The objective of this study was to demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As research shows, the cumulative impact of the pandemic on consumer behavior has significant implications for business. Companies can no longer defend their pricing policies with factors that no longer have a benefit and are not crucial to a consumer in the new reality [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As research shows, the cumulative impact of the pandemic on consumer behavior has significant implications for business. Companies can no longer defend their pricing policies with factors that no longer have a benefit and are not crucial to a consumer in the new reality [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this paper, we aimed to outline a possible approach for this situation in order to improve operations and production management. In parallel, other researchers, such as Ślusarczyk, plan to begin research in the same subject area this year: "In the further perspective, the authors suggest expanding the analysis and conducting additional research that will allow for the identification of the links between specific i4.0 technologies as well as the required competences and skills of employees" [77] (p. 13). Due to the activity of several researchers in this field, further research steps can be expected in the coming years by intensifying the discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Ślusarczyk et al (2021) found differences in levels of employee training in anticipating the implementation of the latest technologies under the I4.0 regime. For instance, training in stress management or training for management staff was much more prominent among Malaysian companies (Ślusarczyk et al , 2021). Unsurprisingly, Sung (2018) concluded by making calls for “a cross-national study comparing unique or common features of each nation's Industry 4.0 initiatives […]” (p. 45) that will further illuminate I4.0 research.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Ślusarczyk et al (2021) studied employee preparedness for I4.0, making comparisons between Polish and Malaysian firms. Ślusarczyk et al (2021) found differences in levels of employee training in anticipating the implementation of the latest technologies under the I4.0 regime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation